2018
DOI: 10.1039/c8tc01502c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin film heterojunctions by combining solution processing and sublimation for ambipolar organic field-effect transistors

Abstract: Evaporation of small molecular n-type naphthalene on spin-cast p-type poly(3-hexylthiophene) fibers for bulk-like heterojunction ambipolar field-effect transistors with balanced electron and hole transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The ambipolar concept of hybrid heterojunction film derived from codeposited solution processable binary polymer blends is attractive for achieving large‐area integrated circuits on account of simple fabrication procedures . Nevertheless, it is difficult to control the microstructure and surface arrangement of the two semiconductors and hence the morphology of semiconducting thin film, which is crucial for balanced carrier transfer.…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…The ambipolar concept of hybrid heterojunction film derived from codeposited solution processable binary polymer blends is attractive for achieving large‐area integrated circuits on account of simple fabrication procedures . Nevertheless, it is difficult to control the microstructure and surface arrangement of the two semiconductors and hence the morphology of semiconducting thin film, which is crucial for balanced carrier transfer.…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…21,[23][24][25] More broadly, blending a conductive polymer with a nonconjugated system is used to acquire new mechanical, optical, morphological and thermal properties, or to introduce strategic intermolecular forces for adhesion/binding, coulombic charge stabilization, or promote desired chemical-electrochemical reactions. 26 Conventional macroscopic electroanalytical methods, notably cyclic voltammetry, are typically used as the main tool to study the properties of conductive polymer electrodes and compare behavior across materials sets to elucidate electrochemical structure-property relationships. As explored herein, the nanoscale spatial-heterogeneity arising from phase segregation in polymer blend electrodes can be addressed most powerfully using the local electrochemical technique scanning electrochemical cell microscopy (SECCM) 27,28 to fully understand the relationship between local chemical composition and electrochemical reactivity.…”
Section: Abstract: Scanning Electrochemical Cell Microscopy; Seccm; Ementioning
confidence: 99%
“…Herein, the nanoscale electron-transfer kinetics of a model system has been considered: blends of a semicrystalline conductive polymer, P3HT, and amorphous insulator poly­(methyl methacrylate) (PMMA). P3HT was chosen as the model conductor for organic electrochemical systems as it is well-studied, both structurally and electrochemically (at the macroscale). ,, As the interest is on nanoscale behavior and connections to UME arrays, P3HT was blended with PMMA, as the system is known to possess microstructural heterogeneity arising from phase segregation. , Previously, P3HT/PMMA microstructural domains have been used to improve charge transport in organic field effect and electrochemical transistors, to obtain high transmittance while retaining conductivity in optoelectronics, and to alter photoluminescence. , More broadly, blending a conductive polymer with a nonconjugated system is used to acquire new mechanical, optical, morphological and thermal properties or to introduce strategic intermolecular forces for adhesion/binding, Coulombic charge stabilization, or promote desired chemical-electrochemical reactions …”
mentioning
confidence: 99%
“…Heterocyclic or aromatic extension of the naphthalene cores may, however, change their charge transfer characteristics from n-type to p-type by shifting NDIs' energy levels (Suraru et al, 2011;Al Kobaisi et al, 2016). The motivation to study the blend of the core-unsubstituted NDIC8 doped with P3HT was, however, to further explore a potential of alkylated NDIs as n-type semiconductors in hybrid systems, as indicated in our previous works (Janasz et al, 2018). Previously we have demonstrated that adding small quantities of NDIs in P3HT can enhance hole transport in the P3HT:NDI blends (Chlebosz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%